CANADIAN GOVERNMENT ACCOUNTING: A SYSTEMATIC REVIEW - Nasreen, Taslima; Baker, Ron (Copernican Journal of Finance & Accounting, 2022)
This paper systematically reviews government accounting research in a developed economy, Canada, and suggests ways to advance knowledge in this area. The purpose of this study is to provide researchers with an up-to-date overview of the field of Canadian government accounting research. The methodology consisted of a structured literature search to select and analyze academic papers according to the thematic objectives of this study. Our review covers 29 articles published in accounting, finance, and public administration journals over 42 years. To the best of our knowledge, no systematic review has been done in Canadian government accounting. This study examines Canadian government accounting research coverage in financial, managerial, and auditing categories to date. This review identifies some under-explored areas, such as political influence on government managerial accounting practice, as well as unexplored areas, such as the influence of the internationally accepted conceptual framework on the quality of government accounting. This study contributes to the literature on government accounting by providing a review of the current literature and suggesting future research areas. This will be useful to researchers and practitioners in government accounting.